Ketika Kekayaan Alam Tidak Menyejahterakan: Pembelajaran dari Pencegahan Korupsi Sektor Sumber Daya Alam - Pradiptyo, Rimawan; Saputra, Wiko; Nugroho, Aryanto; Hutami, Aldila (Integritas : Jurnal Antikorupsi, 2019)
The natural resource sector dominates the Indonesian economy. However, its state revenue is suboptimum under the existing management. The corruption prevention program of the KPK National Rescue Movement, aims at improving governance in the natural resources sector to increase state revenue. This study analyzes the program achievements in fiscal policy and state revenue in the forestry sector, oil palm plantations, mining, and marine and fisheries. The program has increased state revenue of Rp 22,64 trillion in the 2015-2017 period, consisting of tax revenue of Rp 8,82 trillion and non-tax state revenue of Rp 13,82 trillion. The program has improved the licensing system, developing an information system for state revenue, data exchange, and synergy across ministries. These achievements, however, have been sub-optimum in closing the loopholes of state revenue losses and building a credible fiscal policy. Further improvement in institutional aspects should be conducted to optimize the state revenue.